Аспекти інформаційно-психологічного впливу в Стратегії кібербезпеки України - Шаховал, Олександра; Гнатюк, Сергій (Видавництво Львівської політехніки, 2016)
In this paper the aspects of information-psychological impact in a cybersecurity strategy for Ukraine are analyzed. The possible ways of impact individual, society, state and ways and means of protection against it, which provides document, are shown.
Keywords: стратегія кібербезпеки; інформаційно-психологічний вплив